Responsible Accounting in the Hospitality Industry - Pajrok, Andor (Journal of Education Culture and Society, 2020)
Nowadays, due to globalization and intensified market competition, management attention has to be focussed on efforts where they will do the most good. In order to survive, especially in the service industry, Managers in the new business environment need more relevant cost and performance information on the organization’s activities, processes, products/services and customers. The task of management accounting is to prepare this accounting information, which has the possibility to indicate what costs, revenues and results should be. Responsible accounting is an underlying concept of accounting performance measurement systems. The basic idea is that large diversified organizations are difficult, if not impossible to manage as a single segment, thus they must be decentralized or separated into manageable parts. These parts or segments are referred to as responsibility centers that include: revenue centers, cost centers, profit centers and investment centers. This approach allows responsibility to be assigned to the segment managers that have the greatest amount of influence over the key elements to be managed. These elements include revenue for a revenue center, costs for a cost center, a measure of profitability for a profit center and return on investment for an investment center.